It's okay to be different - Parr, Todd. (Boston : Little, Brown, 2001)
Illustrations and brief text describe all kinds of differences that are "okay," such as "It's Okay to be a different color," "It's Okay to need some help," "It's Okay to be adopted," and "It's Okay to have a Different nose."
Keywords: Self-esteem -- Fiction; Individuality -- Fiction